2014
DOI: 10.1007/s10943-014-9839-x
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Spirituality and Depression in Parents Caring for Children with Developmental Disabilities: Social Support and/or Last Resort

Abstract: Aims: Associations between spirituality and depression were examined in parents of children with developmental disabilities using both quantitative and qualitative methodology. Results: Spirituality was positively associated with depression, whereas social support was negatively related; parents with higher spiritual beliefs and lower levels of support had higher depression scores. Themes emerging from interviews were spiritual/religious coping as a way of dealing with difficulty, as a last resort, and as a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 56 publications
(67 reference statements)
0
12
0
2
Order By: Relevance
“…While this difference has been found, mothers and fathers were both shown to be actively coping, showing engagement, and using coping strategies (Sullivan, ). This broad literature on coping strategies used by mothers suggests that there may be different types of coping, including internal efforts to manage stress (Woodman & Hauser‐Cram, ), seeking support from outside sources (Findler, Jacoby, & Gabis, ), and turning to religion or spirituality for guidance (Gallagher, Phillips, Lee, & Carroll, ). Although some studies have examined coping strategies in mothers of children with special needs, fewer studies are specific to mothers of children with Down syndrome.…”
Section: Contextual Model Of Family Stressmentioning
confidence: 99%
“…While this difference has been found, mothers and fathers were both shown to be actively coping, showing engagement, and using coping strategies (Sullivan, ). This broad literature on coping strategies used by mothers suggests that there may be different types of coping, including internal efforts to manage stress (Woodman & Hauser‐Cram, ), seeking support from outside sources (Findler, Jacoby, & Gabis, ), and turning to religion or spirituality for guidance (Gallagher, Phillips, Lee, & Carroll, ). Although some studies have examined coping strategies in mothers of children with special needs, fewer studies are specific to mothers of children with Down syndrome.…”
Section: Contextual Model Of Family Stressmentioning
confidence: 99%
“…Salah satunya penelitian yang dilakukan oleh Gallagher et al (2015) dengan metode kuantitatif dan kualitatif terhadap 32 orang tua dengan anak yang mengalami gangguan perkembangan, penelitian ini menunjukan terdapat hubungan positif antara spiritual dengan tingkat depresi orang tua artinya semakin tinggi tingkat spiritual orang tua semakin rendah tingkat depresinya. Penelitian serupa dilakukan oleh Sugianto (2014) tentang pengaruh konseling spiritual perawat terhadap tingkat kecemasan pada keluarga pasien yang dirawat di ruang ICU RSUD Sleman Yogyakarta dengan metode quasi ekperimen terhadap 20 responden menunjukan hasil bahwa terdapat pengaruh konseling spiritual perawat terhadap tingkat kecemasan pada keluarga pasien.…”
Section: Pendahuluanunclassified
“…Mothers of children with intellectual disabilities (ID) were significantly less happy [8], and parents of children with Autism Spectrum Disorder experienced higher levels of anxiety and stress [9,10] and also more parental stress than parents of children with TD or children with other clinical conditions such as Down syndrome, behavior disorders, ID [11,12]. In general, mothers and fathers raising children with DD report poorer physical health than parents of children with TD [7,13,14]. The limited previous research on FA in parents of children with DD showed that mothers’ anxieties were primarily connected with the child: his or her quality of life in the future, self-reliance, education, relationships with others, possibilities of employment, or financial prospects [15,16,17,18,19,20,21,22,23,24,25].…”
Section: Introductionmentioning
confidence: 99%